TOBACCO INTAKE STATUS–A REVIEW - KUMARESAN, C. (International Journal of Current Pharmaceutical Research, 2019)
One of the global health issues is tobacco consumption, either in the form of smoked tobacco and smokeless tobacco (ST). In the world wide more than 300 million people consumes various ST product. Tobacco makes addiction and cause cancer, the cardiovascular mortality risk level more and poor pregnancy outcomes. The smoked tobacco and ST causes major disease burden in different countries and regions. This article reviews briefly about the various health issues causes by tobacco products consumption and its effects of stimulating diseases.